Unique case of takayasu arteritis with bilateral carotid stenosis - Chitnavis, Aditya; Dodhia, Aditya; Vashishta, Apoorva (Indian Journal of Case Reports, 2025)
Takayasu’s arteritis (TAK) is a chronic, multifactorial vasculitis of the large vessels of the body, sometimes affecting the medium vessels. Thus, the most commonly afflicted vessel is the aorta and its branches. It is typically encountered in the young to middle-aged population, with a higher tendency for females. In this case report, we have a post-menopausal South Asian female, who presented with left hemiparesis following a fall. Magnetic resonance imaging of the brain did not reveal any parenchymal involvement but magnetic resonance angiography revealed severe stenosis in bilateral common carotid arteries (CCA), later confirmed by digital subtraction angiography. Imaging supplemented by clinical features and elevated inflammatory markers confirmed our diagnosis of TAK of the CCAs but without aortic infliction. This case underscores the importance of high clinical suspicion, early recognition, and aggressive treatment of TAK to prevent adverse events and improve patient outcomes. Regular follow-up and monitoring of inflammatory markers and imaging studies are crucial in managing this chronic condition.